Analisis Penerapan Pembatalan Sertipikat Hak Milik Demi Kepastian Hukum Pada Kantor Wilayah Badan Pertanahan Nasional Provinsi Sumatera Utara - Rosalia Ena Darmawati Br Jabat; Dayat Limbong; Isnaini Isnaini (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of the study was to analyze the legal arrangements for cancellation of property rights certificates, analyze the legal consequences of cancellation of property rights certificates and analyze the application of cancellation of property rights certificates at the North Sumatra Provincial BPN Regional Office. The research method used is normative legal research, with a statutory and case approach, data collection techniques are interviews and documentation studies, while data analysis uses descriptive analysis. This research shows that the legal regulations regarding the cancellation of the Hak Milik certificate have undergone many changes. Currently, the regulation used is Permen ATR/BPN Number 21 of 2020 concerning Handling and Settlement of Land Cases. As a result of the cancellation of the certificate of ownership, the land status returns to land which is directly controlled by the state if the ownership status of the certificate is null and void by law. Meanwhile, if the ownership status of the rights requested for cancellation has been certified, the Land Office and the Provincial BPN Regional Office will issue a cancellation decree to revoke the status of rights to ownership of the Property Rights certificate. The application of the cancellation application process and considerations in issuing the Cancellation Decree which is the Authority of the Regional Office to cancel the certificates issued by the North Sumatran Regency/City Land Offices can be categorized into two types of cancellations. First, a decision whose ruling expressly states the void/illegitimate object of the case for which cancellation is being requested. Second, the decision whose ruling is not clear declares that the object of the case for which cancellation is being requested is null and void. The suggestion from this research is that there are contradictory rules between PP No. 18 of 2021 and Permen ATR No. 21 of 2020 regarding the cancellation of land rights due to administrative defects, which can only be done before a period of 5 years from the date of issuance so that it is synchronized with Permen ATR/BPN No. 21 of 2020 , so as not to create a gap to be able to file a counterclaim on the Cancellation Decree that has been issued.